ANALISIS KELAYAKAN PEMBERIAN KREDIT UNTUK PROYEK PEMBANGUNAN FIBER OPTIK SEPANJANG REL KERETA API DI PULAU JAWA MILIK PT INTEGRASI JARINGAN EKOSISTEM - Akbar Ibrahim; Muchlis Muchlis (Ibs Press, 2023)
This study aims to analyze the financing feasibility of the fiber optic cable network development project that will be carried out by PT Integrasi Jaringan Ekosistem which will be financed by the Bank. Therefore this study is for academic purposes so that the assumptions used are the assumptions of the lending bank in accordance with the provisions that apply to the bank. The analysis used in granting credit includes management analysis, industry analysis, risk analysis and project feasibility analysis. The financial aspect is based on the calculation of NPV, IRR, PI and PP. From the calculation results and several assumptions, it is concluded that this project is feasible to run and obtain financing from the Bank. In addition, a sensitivity analysis is carried out to find out how far the investment can remain feasible if there are several changes in conditions or variables. The implication of this research, it is hoped that the Bank as a financier will get an idea of the feasibility of the project and the benefits that can be obtained, and for PT Integrasi Jaringan Ekosistem can facilitate the planning, execution of work, monitoring, and also project control.